Blockchain as a decentralized communication tool for sustainable development - Yousef A. Baker, El-Ebiary; Amer, Hatamleh; Khairi, Aseh; Abdullah, Altrad; Khalid Thaher, Amayreh; Rajina R., Mohamed; Pathmanathan, P.R.; Lowai Saleh, Aledinat (2021)
This research introduces the distributed ledger technology ( blockchain ) in terms of sustainable development in the future. This study is based on private, public and global communications in various industries. The growing demands for secure and decentralized transactions around the world demonstrate the need for Blockchain technology as a medium of operations and communications. The blockchain system is completely decentralized and allows users to exchange messages in an efficient and secure manner. The highlight of the paper is the anticipated future use of blockchain networks as a communication tool in every business and digital economy for a safe and sustainable development, while presenting its advantages and limitations that have been confirmed based on the experiences of various experts. Moreover, the article provides recommendations for the use of blockchain to greatly complicate its identification in future communications. The paper also concludes that the use of the blockchain system could be beneficial and enhance future communications and digital technologies.